2013
DOI: 10.1073/pnas.1304322110
|View full text |Cite
|
Sign up to set email alerts
|

Hammondia hammondi , an avirulent relative of Toxoplasma gondii , has functional orthologs of known T. gondii virulence genes

Abstract: Toxoplasma gondii is a ubiquitous protozoan parasite capable of infecting all warm-blooded animals, including humans. Its closest extant relative, Hammondia hammondi, has never been found to infect humans and, in contrast to T. gondii, is highly attenuated in mice. To better understand the genetic bases for these phenotypic differences, we sequenced the genome of a H. hammondi isolate (HhCatGer041) and found the genomic synteny between H. hammondi and T. gondii to be >95%. We used this genome to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 40 publications
(71 reference statements)
2
70
0
1
Order By: Relevance
“…Our recently published genome sequence of an isolate of H. hammondi (HhCatGer041 [28]; GenBank accession number AVCM00000000.1) revealed a high degree of genomic synteny and conservation with T. gondii, further confirming H. hammondi as the closest known extant relative of T. gondii (28). Despite this high sequence similarity, there are dramatic phenotypic differences between H. hammondi and T. gondii.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Our recently published genome sequence of an isolate of H. hammondi (HhCatGer041 [28]; GenBank accession number AVCM00000000.1) revealed a high degree of genomic synteny and conservation with T. gondii, further confirming H. hammondi as the closest known extant relative of T. gondii (28). Despite this high sequence similarity, there are dramatic phenotypic differences between H. hammondi and T. gondii.…”
Section: Discussionmentioning
confidence: 93%
“…In the ROP18 gene there is a 107-bp sequence present in T. gondii strains that actively express ROP18 (such as strain types I and II [15,23]) as well as HhROP18 (28) but absent in T. gondii strains that do not express ROP18 (such as members of the type III lineage [15,23]). The HhROP18 promoter is fully active in luciferase reporter assays and drives HhROP18 protein expression in T. gondii, and this dramatically alters virulence; this 107-bp sequence is both necessary and sufficient for ROP18 promoter-driven reporter expression (28). In the present study, we found that the 16 bp deleted in the HhROP16 promoter play an important role in the ability of the ROP16 upstream sequence to drive reporter gene expression, suggesting that this is an important core promoter sequence for ROP16.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations